Synthesis and corrosion inhibition studies of 1-(4-chlorobenzoyl)thiourea derivatives on mild steel in 1.0 M HCL - Hashim S.N.M.; Jumal J.; Kassim K. (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA